2016
DOI: 10.1097/pcc.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Can Monitoring Fetal Intestinal Inflammation Using Heart Rate Variability Analysis Signal Incipient Necrotizing Enterocolitis of the Neonate?

Abstract: We identified a unique subset of fetal heart rate variability measures reflecting 1.5 days ahead of time the levels of macrophage activation and increased leakiness in terminal ileum. We propose that such subset of fetal heart rate variability measures reflects brain-gut communication via the vagus nerve. Detecting such noninvasively obtainable organ-specific fetal heart rate variability signature of inflammation would alarm neonatologists about neonates at risk of developing necrotizing enterocolitis and seps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Several other studies have measured autonomic tone changes among infants at risk for prematurity-related complications. In an instrumented fetal sheep model, Liu et al 19 described significant decreases in fetal HRV from 1.5 days before the onset of intestinal NEC changes. In a cohort of premature infants, Doheny et al 7 found that depressed vagal tone (HF HRV power) 7,12 in the early postnatal period (5-8 days of life) predicted later-onset NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have measured autonomic tone changes among infants at risk for prematurity-related complications. In an instrumented fetal sheep model, Liu et al 19 described significant decreases in fetal HRV from 1.5 days before the onset of intestinal NEC changes. In a cohort of premature infants, Doheny et al 7 found that depressed vagal tone (HF HRV power) 7,12 in the early postnatal period (5-8 days of life) predicted later-onset NEC.…”
Section: Discussionmentioning
confidence: 99%
“…As positive and negative tissue controls, brain tissues from a different fetal sheep study being performed in our laboratory were run concurrently with UCO and control animals. In this study, afferent (positive control) and efferent (negative control) bilateral cervical vagus nerve stimulation (VNS) was accompanied by intravenous injection of endotoxin to trigger inflammatory response in fetal sheep near term [ 45 , 46 , 52 , 53 ]. Twelve dilutions of c-Fos antibody were tested with various antigen retrieval methods.…”
Section: Methodsmentioning
confidence: 99%
“…[ 4 6 ] CAP activity is reflected in fetal heart rate (FHR) variability (fHRV). [ 7 ] [ 8 ] [ 9 ] HRV measures can be derived from various signal-analytical domains such as statistical, informational, invariant or energetic. [ 8 ] [ 9 ] However, among many dozens HRV measures that have been deduced mathematically over the past several decades, it is not known a priori which fHRV measures reflect physiologically relevant processes such as inflammation.…”
Section: Introductionmentioning
confidence: 99%